Dynamics Modeling and Control of a Quadrotor with Swing Load. (17th November 2014) - Sadr, S.; Moosavian, S. Ali A.; Zarafshan, P.
Abstract : Nowadays, aerial robots or Unmanned Aerial Vehicles (UAV) have many applications in civilian and military fields. For example, of these applications is aerial monitoring, picking loads and moving them by different grippers. In this research, a quadrotor with a cable-suspended load with eight degrees of freedom is considered. The purpose is to control the position and attitude of the quadrotor on a desired trajectory in order to move the considered load with constant length of cable. So, the purpose of this research is proposing and designing an antiswing control algorithm for the suspended load. To this end, control and stabilization of the quadrotor are necessary for designing the antiswing controller. Furthermore, this paper is divided into two parts. In the first part, dynamics model is developed using Newton-Euler formulation, and obtained equations are verified in comparison with Lagrange approach. Consequently, a nonlinear control strategy based on dynamic model is used in order to control the position and attitude of the quadrotor. The performance of this proposed controller is evaluated by nonlinear simulations and, finally, the results demonstrate the effectiveness of the control strategy for the quadrotor with suspended load in various maneuvers.